Coffee Drying Tool with LQR-PID Control - Rama Arya Sobhita; Sindy Yurisma Sheila; Anggara Trisna Nugraha; Rachma Prilian Eviningsih (MEIN : Journal of Mechanical, Electrical & Industrial Technology, 2024)
Indonesia ranks as the third largest coffee bean producer globally due to its favorable climate for coffee cultivation and production. The drying process is one of the crucial stages in coffee bean processing as it significantly impacts the bean's quality. This study focuses on optimizing the drying process through the implementation of a sun tracking system mechanism. In essence, a sun tracking system is employed to maximize sunlight exposure by controlling the tray's position to constantly align with the sun's movement. The constructed system comprises both mechanical and electrical components. The control methods utilized in this system involve LQR and PID control. Experimental results will be analyzed to determine which controller yields the best performance.